A Call to Action to Bring Safer Parenteral Micronutrient Products to the U.S. Market. (August 2015) - Vanek, Vincent W.; Borum, Peggy; Buchman, Alan; Fessler, Theresa A.; Howard, Lyn; Shenkin, Alan; Valentine, Christina J.; ,
The American Society for Parenteral and Enteral Nutrition (A.S.P.E.N.) started an intensive review of commercially available parenteral vitamin and trace element (TE) products in 2009. The chief findings were that adult multi-TE products currently available in the United States (U.S.) provide potentially toxic amounts of manganese, copper, and chromium, and neonatal/pediatric multi-TE products provide potentially toxic amounts of manganese and chromium. The multivitamin products appeared safe and effective; however, a separate parenteral vitamin D product is needed for those patients on standard therapy who continue to be vitamin D depleted and are unresponsive to oral supplements. The review process also extended to parenteral choline and carnitine. Although choline and carnitine are not technically vitamins or trace elements, choline is an essential nutrient in all age groups, and carnitine is an essential nutrient in infants, according to the Food and Nutrition Board of the Institute of Medicine. A parenteral choline product needs to be developed and available. Efforts are currently under way to engage the U.S. Food and Drug Administration (FDA) and the parenteral nutrient industry so A.S.P.E.N.'s recommendations can become a commercial reality.